Empresa agrária: tratamento jurídico diferenciado à luz do artigo 170, IX e artigo 179 da Constituição Federal Brasileira - Amorim, Eliette Rodrigues de (2012)
The present dissertation has for objective to analyze the agrarian company in the Brazilian Agrarian Right and especially in the Commercial Right, explaining yours beginnings, juridical foundations and peculiar characteristics of the managerial agrarian activity in relation to the other species of Brazilian companies. The objective is to demonstrate that the differentiated juridical treatment granted in general to the small companies, just as having indicated in the article 179, combined with the article 170, IX, of the Constitution, is specifically necessary to the agrarian company, turning its economic function more effective and significant in the accomplishment of the social justice.